Pengaruh Green Product, Brand Image dan Environmental Awareness terhadap Purchase Intention BudiSun Resort Maumere - Dimas Realino; Yohanes Pieter Pedor Parera (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
The issue of climate change and increasing public awareness of the importance of environmental sustainability are driving the tourism industry to adopt sustainable practices. One such effort is the use of environmentally friendly products or green products in its operations. BudiSun Resort Maumere, located in East Nusa Tenggara, is one resort that has implemented environmentally friendly principles in its services and facilities. However, further research is needed to determine the extent to which these practices influence consumer behavior, particularly in terms of purchase intention. This study aims to analyze the influence of green products, brand image, and environmental awareness on consumer purchase intention at BudiSun Resort Maumere. The research approach used was quantitative with a survey method. The sample in this study consisted of 150 respondents who had stayed at the resort. The instrument used was a questionnaire with a Likert scale, and the data were analyzed using multiple linear regression with the help of SPSS version 25 software. The analysis results showed that all three independent variables—green product, brand image, and environmental awareness—simultaneously had a significant effect on purchase intention, with a coefficient of determination (R²) of 0.827 and an F-value of 231.894 at a significance level of 0.000. Partially, brand image (β = 0.321; sig = 0.000) and environmental awareness (β = 0.651; sig = 0.000) had a positive and significant effect on purchase intention. However, green product (β = –0.056; sig = 0.354) did not show a significant effect. These findings suggest that while the use of environmentally friendly products is important, the strength of brand image and consumer environmental awareness play a greater role in influencing consumer intention to revisit resort services. Therefore, sustainable tourism marketing strategies should emphasize strengthening brand image and environmental education.